2000
DOI: 10.1381/096089200321593698
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Laparoscopic Adjustable Gastric Banding for Severe Obesity: Postoperative and Retrospective Preoperative Evaluations

Abstract: Postoperative psychosocial quality is at a level that may be expected to motivate patients to consolidate the surgically established weight reduction, but attention should be paid to the physical condition. Since the relative gain in quality of life as experienced by patients tends to be evaluated less with a longer duration of the postoperative interval, the risk of relapse may increase with passage of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“…Several authors showed an improving mental health and quality of life by the first year that eroded over the subsequent years. [22][23][24][25][26][27] In our cross-sectional study, performed a mean of 8.7 years after the operation, we were able to show that a more impaired health and psychological status was present in those operated more than 5 years ago compared to subjects operated more recently. The time lapse since operation played an important role as health status scores showed a higher physical, emotional and social dysfunction in those operated more than 5 years ago and out of the psychological features sensitivity was also more present in these subjects.…”
Section: Discussionmentioning
confidence: 55%
“…Several authors showed an improving mental health and quality of life by the first year that eroded over the subsequent years. [22][23][24][25][26][27] In our cross-sectional study, performed a mean of 8.7 years after the operation, we were able to show that a more impaired health and psychological status was present in those operated more than 5 years ago compared to subjects operated more recently. The time lapse since operation played an important role as health status scores showed a higher physical, emotional and social dysfunction in those operated more than 5 years ago and out of the psychological features sensitivity was also more present in these subjects.…”
Section: Discussionmentioning
confidence: 55%
“…This condition is associated with an increased risk of morbidity and mortality from numerous related medical conditions, such as diabetes, coronary artery disease, and several types of cancer; morbid obesity is also related to debilitating psychosocial consequences (11) . Poor HRQL has been repeatedly documented in obese patients (21) , and HRQL impairment relates to increasing BMI (12) . Unfortunately, morbidly obese patients respond poorly to traditional dietary and exercise weight-loss regimens, and when an initial response occurs, it is likely to be poorly maintained (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the SOS study (EC IIa), 55 three EC IIb studies 58,64,101 and three EC III studies 54,59,102 focused on aspects of general QoL. The SOS study 5,55 applied a battery of generic and study-specific self-assessment instruments or subscales in order to characterize various aspects of QoL such as health perception, mental well-being/mood disorders, eating behavior, and psychosocial functioning in the severely obese.…”
Section: General Quality Of Lifementioning
confidence: 99%
“…QoL improved after 2 and 4 y by substantial weight loss. 74 The results of the other six studies 54,58,59,64,101,102 are based on a single standardized questionnaire such as the SF-36, 54,101,102 the Gothenburg Quality of Life Scale, 59 or the Bariatric Analysis and Reporting Outcome System (BAROS), 58 and yielded significant improvements of QoL in the majority of bariatric patients at follow-up.…”
Section: General Quality Of Lifementioning
confidence: 99%